Asah Kreativitas Kelompok Remaja Masjid Melalui Pelatihan Canva - Murdowo, Sugeng; Arifin, Wafi; Wahjono, Wahjono; Afrianto, Syahrul; Rizki, Desta Surya; khasanah, fata nidaul (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2025)
Youth play a vital role in the development of a nation. Those with high levels of productivity need to be facilitated and empowered so that their potential can be maximized. Digital literacy has now become an essential skill not only for academics but also for the general public. A strong understanding of digital literacy is necessary to optimize the use of text, numerical data, and technology in both learning and daily activities. The implementation of this program involves the participation of mosque youth groups in addressing existing challenges, particularly the need for training on the use of technology that can generate positive impacts. The methods applied include observation, socialization, training, mentoring, and evaluation. The evaluation through discussion revealed the enthusiasm of the partners in participating in the training activities. Meanwhile, the questionnaire results indicated that the partners recognized the benefits of the program and the supporting facilities provided for digital literacy activities, with a satisfaction rate of 100%.